La0.7Sr0.3MnO3 nanoparticles coated with fatty amine - Rajagopal, Rajashree; Mona, J.; Kale, Sangeeta N.; Bala, Tanushree; Pasricha, Rem; Poddar, P.; Sastry, M.; Bhagavatula L. V. Prasad; Kundaliya, Darshan C.; Ogale, S. B. (Applied Physics Letters, 2006)
We report on the synthesis of La0.7Sr0.3MnO3 (LSMO) nanoparticles having perovskite structure and particle size of the order of 30 rim. The process involves citrate-gel synthesis, size filtering, and; surface coating with a shell of octadecyl amine (ODA) using electrostatic interaction-assisted novel chemical route. Magnetic measurements show the Curie temperature of similar to 360 K establishing the desired stoichiometry and phase. Fourier transform infrared-studies bring out. that the amine group of ODA interacts with the LSMO surface. Refluidization yields uniform redispersion of the coated and dried powder. (c) 2006 American Institute of Physics.

Low temperature route to prepare LaMnO3 - Daundkar, A.; Kale, Sangeeta N.; Gokhale, Suresh P.; Ravi, V (Materials Letters, 2006)
A combination of digestion and further low temperature calcination to crystallize the product is employed to prepare LaMnO3(LM) ceramics. Freshly co-precipitated lanthanum and manganese hydroxides gel is allowed to react at 100 degrees C under refluxing and stirring conditions for 6-12 h. The X-ray amorphous product so formed is heated at 300 degrees C to form crystalline LM powders. This is the lowest temperature so far reported for the formation of LaMnO3. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for the calcined powders. (c) 2005 Elsevier B.V All rights reserved.
Keywords: Chemical synthesis; LaMnO3; Precipitation; transmission electron microscopy; X-ray diffraction

La0.67Ce0.03Sr0.3MnO3-coupled microwave assisted ultra-fast synthesis of nanocrystalline cobalt oxide and Bismuth oxide - Rajagopal, Rajashree; Mona, J.; Joshi, Rakesh S.; Kale, Sangeeta N.; Pradhan, Sivararn; Gaikwad, A. B.; Ravi, V. (Materials Letters, 2008)
Bismuth hydroxide and Cobalt hydroxide gels were freshly prepared by adding aqueous sodium hydroxide to their corresponding nitrates under basic conditions. Then they were oven dried at 373 K and found to be amorphous in X-ray diffraction (XRD) study. They crystallized into their respective oxides by microwave irradiation (2.45 GHz) in merely 2 min using La0.67Ce0.03Sr0.3MnO3 (LCSMO) as couplant in a microwave domestic oven (similar to 100 W). This is the lowest temperature treatment and synthesis time so far reported in the literature for the formation of these systems. Formation of nanocrystallites of Bi2O3 (10 nm) and Co3O4 (15 nm) has been confirmed by XRD. Normally these hydroxides produce oxides only on heating at temperature >673 K or digesting them at 373 K for 4 - 6 hours as reported by us earlier. Microwave assisted heating proves to be a novel technology whose applications can be carefully harnessed due to its unique effects compared to the conventional heating, such as rapid volumetric heating, shortened reaction time and energy saving. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; Manganites; Microwave; Oxides